Strengthening the Role of Students in Environmental Conservation through Environmental Education and Sustainable Tree-Planting Actions - Ayu Winda Rizky; Wardayani Wardayani; Mesran Mesran; Dian Purnama Sari; Rizkah Fadillah; Mime Azrina Jaafar; Rosnizam Rosnizam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Environmental degradation and the declining quality of urban green spaces require collaborative conservation initiatives involving higher education institutions and university students. This community service program aimed to strengthen the role of students in environmental conservation through environmental education and sustainable tree-planting activities conducted at Medan Urban Forest on 22 June 2026 involving fifteen students from the Management Study Program of Sekolah Tinggi Ilmu Manajemen Sukma. The program employed an integrated approach consisting of environmental education, participatory discussions, practical planting of mango (Mangifera indica) and mangosteen (Garcinia mangostana) trees, and post-activity evaluation. The results demonstrated significant improvements in participants' environmental competence, with ecosystem knowledge increasing from 41% to 85%, environmental awareness from 65% to 98%, environmental responsibility from 35% to 100%, and environmental empathy from 51% to 78%. Participant satisfaction was also highly positive, with 55% reporting being very satisfied, 34% satisfied, and 11% moderately satisfied with the implementation of the program. These findings indicate that integrating environmental education with experiential conservation activities effectively enhances environmental literacy, strengthens pro-environmental attitudes, and encourages active participation in sustainable environmental stewardship. Therefore, this community service program provides a practical and replicable model for universities seeking to integrate environmental education, student empowerment, and community engagement in support of sustainable urban environmental conservation.